1983
DOI: 10.1056/nejm198302243080802
|View full text |Cite
|
Sign up to set email alerts
|

Polyspecificity of Monoclonal Lupus Autoantibodies Produced by Human-Human Hybridomas

Abstract: We studied the serologic properties of monoclonal autoantibodies that were produced by hybridomas derived from lymphocytes of patients with systemic lupus erythematosus. The hybridomas were made by fusion of a human lymphoblastoid cell line, GM 4672 (derived from a patient with multiple myeloma), with peripheral-blood or splenic lymphocytes from six patients with lupus. Thirty monoclonal autoantibodies, selected for their ability to react with denatured DNA, were analyzed. Eighteen of them reacted with three o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(114 citation statements)
references
References 28 publications
5
108
1
Order By: Relevance
“…However, analyses using hybridomaderived monoclonal antibodies have shown that the diversity of lupus autoantibodies is restricted (18,23). For example, monoclonal autoantibodies that were selected for their ability to bind to ssDNA may also bind to the phospholipid cardiolipin and demonstrate features of a lupus anticoagulant (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, analyses using hybridomaderived monoclonal antibodies have shown that the diversity of lupus autoantibodies is restricted (18,23). For example, monoclonal autoantibodies that were selected for their ability to bind to ssDNA may also bind to the phospholipid cardiolipin and demonstrate features of a lupus anticoagulant (24).…”
Section: Discussionmentioning
confidence: 99%
“…Three weeks later, a booster injection of I /Lg of SA-I in phosphate buffered saline (PBS) was administered to the hind footpads (8). The presence of autoantibodies against single-stranded DNA, dsDNA, poly(l), poly(G), histones (subfractions Hl-H5), cardiolipin, Sm, RNP, SS-A/Ro, SS-B/La, and 16/6 Id idiotype in the serum was determined by enzyme-linked immunosorbent assay (ELISA) (5,6,8,20,21). The mice were bled through their orbits, with 300 /Ll of serum obtained from each animal.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence and the clinical importance of these antibodies have also been discussed in relation to the occurrence of human and mouse monoclonal antibodies against denatured DNA, and their cross-reactivity with cardiolipin and other phospholipids (4)(5)(6).…”
Section: Anticardiolipin Antibodies In Patients With Systemic Lupus Ementioning
confidence: 99%